Correlation of Maternal Serum Hepcidin, Soluble Transferrin Receptor (sTfR) and Cholecalciferol with Third Trimester Anemia: Findings from A Nested Case-control Study on A Pregnancy Cohort - Raden Tina Dewi Judistiani; Sefty Mariany Samosir; Setyorini Irianti; Benny Hasan Purwara; Budi Setiabudiawan; Johannes Cornelius Mose; Budi Handono (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Cholecalciferol, hepcidin, and soluble transferrin receptor (sTfR) interaction play an essential role in iron hemostasis. Anemia in pregnancy contributes to morbidity and mortality both for the mother and baby. In this study, we assessed the correlation between hepcidin, sTfR and cholecalciferol in third trimester maternal anemia. We aimed to find the cut-off for hepcidin and sTfR.METHODS: A case-control study involving 56 pregnant women in each anemia and healthy group was nested on a previous larger cohort study in Indonesia. Serum hepcidin, sTfR and cholecalciferol level were measured by enzyme-linked immunosorbent assay (ELISA) method.RESULTS: Serum hepcidin and sTfR level were significantly higher in case group, while serum cholecalciferol level has no difference between the two groups. New cut-off points were found for hepcidin (<15.93 ng/mL) and sTfR level (>2234.45 ng/mL). Low level of hepcidin (OR=5.32) and high level of sTfR (OR=8.28) increase the risk of anemia. High level of sTfR (adjusted OR=4.725; CI 95%=1.730-12.904; p=0.02) was the most important factor contributes to anemia, followed by the low level of hepcidin (adjusted OR=3.677; CI 95%=1.363-9917; p=0.01).CONCLUSION: The high level of sTfR is the most important factor related to anemia in the third trimester, followed by the low level of hepcidin. Low cholecalciferol level tends to favor the incident of anemia. The new cut-off point of third trimester sTfR and third trimester hepcidin were established in this study and may be useful for risk assessment and treatment monitoring for anemia in pregnancy.KEYWORDS: anemia, cholecalciferol, hepcidin, pregnancy, soluble transferrin receptor